2019
DOI: 10.14309/ajg.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation in Patients With Primary Sclerosing Cholangitis: A Pilot Clinical Trial

Abstract: Author Contributions: JRA initiated study concept and design acquisition of data, analysis and interpretation of data, and drafting of the manuscript. YG, ST, MS analyzed and interpreted microbiome sequencing results. BHM, AP and JRM analyzed and interpreted the metabolomics results. MC participated in data acquisition. ZK participated in interpretation of data and critical revision of the manuscript DP and JK provided critical revisions of manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(116 citation statements)
references
References 35 publications
0
114
0
2
Order By: Relevance
“…The open-label experience of IMT in PSC with controlled IBD demonstrated that it was safe and 3 of the 10 patients demonstrated a 50% reduction in alkaline phosphatase. 157 However, larger randomised trials are needed. Similarly, an even smaller experience in HBeAg-positive…”
Section: Human Experience Of Imt In Chronic Liver Diseasementioning
confidence: 99%
“…The open-label experience of IMT in PSC with controlled IBD demonstrated that it was safe and 3 of the 10 patients demonstrated a 50% reduction in alkaline phosphatase. 157 However, larger randomised trials are needed. Similarly, an even smaller experience in HBeAg-positive…”
Section: Human Experience Of Imt In Chronic Liver Diseasementioning
confidence: 99%
“…In this early study of 10 patients who received a single FMT, 30% achieved a reduction in ALP, which was correlated with the extent of donor engraftment. The procedure was safe and well tolerated and opens the door to further investigation in this area …”
Section: Clinical Trials: Translating Precision Medicine Into Practicementioning
confidence: 99%
“…There is reduced bacterial diversity in PSC, and a recent Mdr2 −/− mouse model elegantly demonstrated the overexpression of inflammasome proteins, a phenomenon that could be transferred by fecal microbiota transplantation (FMT) and provides a link between dysbiosis and immune dysregulation in PSC . Very early studies have explored a role for FMT in PSC, but more work is required to develop firm conclusions about any potential role in managing the condition through manipulating the microbiome …”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Cumulative experience from case series and controlled trials shows that FMT is effective when used to treat relapsing CDI [5,6]. The high therapeutic efficacy of FMT for recurrent CDI is an important proof of concept that substantial modification of the gut microbiota can be an effective modality for treatment of other diseases in humans such as primary sclerosing cholangitis, inflammatory bowel disease, and serious antibiotic-associated diarrhea [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%